A, Article Paulina et,al: Indonesia - Adinda, Jelita; Irawan, Fajar Awang (Faculty of Sport and Health Sciences, 2022)
The purpose of this study was to analyze the suitability of the squatting position pointing motion in athletes in Semarang Regency. This type of research is purposive sampling, namely the technique of determining the sample with certain considerations. The method in this research uses descriptive analysis. The results of the analysis of the pointing motion of athletes in Semarang Regency, there were 11 boys and girls, each pointing stage in the kinematic data: 1) time, 2) right arm flexion angle, 3) right knee flexion angle, 4) trunk extension angle 5) extension angle backswing 6) wrist release extension angle 7) ball height. The total number of 11 research samples entered in the